Breast-feeding perceptions, beliefs and experiences of Marshallese migrants: an exploratory study. Issue 16 (27th May 2016) - Scott, Allison; Shreve, Marilou; Ayers, Britni; McElfish, Pearl Anna
Abstract: Objective: To determine perceptions, beliefs and experiences affecting breast-feeding in Marshallese mothers residing in Northwest Arkansas, USA. Design: A qualitative, exploratory study using a brief survey and focus groups. Marshallese women, 18 years or older who had a child under 7 years of age, were included in the study. Setting: Community-based organization in Northwest Arkansas. Results: The majority of mothers viewed breast milk as superior to formula, but had concerns about adequate milk supply and the nutritional value of their milk. The primary barriers to exclusive breast-feeding in the USA included public shaming (both verbal and non-verbal), perceived milk production and quality, and maternal employment. These barriers are not reported in the Marshall Islands and are encountered only after moving to the USA. Breast-feeding mothers rely heavily on familial support, especially the eldest female, who may not reside in the USA. The influence of institutions, including the Special Supplemental Nutrition Program for Women, Infants, and Children, is strong and may negatively affect breast-feeding. Conclusions: Despite the belief that breast milk is the healthiest option, breast-feeding among Marshallese mothers is challenged by numerous barriers they encounter as they assimilate to US cultural norms. The barriers and challenges, along with the strong desire to assimilate to US culture, impact Marshallese mothers' perceptions, beliefs and experiences with breast-feeding.